2022
DOI: 10.3390/rs14174308
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Comparison of Seven Land Surface Evapotranspiration Products in the Haihe River Basin, China

Abstract: Evapotranspiration (ET) is an important part of the surface energy balance and water balance. Due to imperfect model parameterizations and forcing data, there are still great uncertainties concerning ET products. The validation of land surface ET products has a certain research significance. In this study, two direct validation methods, including the latent heat flux (LE) from the flux towers validation method and the water balance validation method, and one indirect validation method, the three-corned hat (TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…GLEAM has been fully validated at the global scale using data of Eddycovariance towers located on different environment (Martens et al, 2017). Thus, recent comparisons of the output of different model simulations have showed that GLEAM reproduces well the magnitude and temporal variability of the available observations (Guo et al, 2022;Liu et al, 2023;Yang et al, 2022). To match the VPD's temporal resolution, these daily data were aggregated to a weekly time scale.…”
Section: Datasets Descriptionmentioning
confidence: 99%
“…GLEAM has been fully validated at the global scale using data of Eddycovariance towers located on different environment (Martens et al, 2017). Thus, recent comparisons of the output of different model simulations have showed that GLEAM reproduces well the magnitude and temporal variability of the available observations (Guo et al, 2022;Liu et al, 2023;Yang et al, 2022). To match the VPD's temporal resolution, these daily data were aggregated to a weekly time scale.…”
Section: Datasets Descriptionmentioning
confidence: 99%